2008
DOI: 10.1080/13674670701250050
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual advisors and old age psychiatry in the United Kingdom

Abstract: This survey investigates the role and views of NHS spiritual advisors across the United Kingdom on the provision of pastoral care for elderly people with mental health needs. The College of Health Care Chaplains provided a database, and questionnaires were sent to 405 registered NHS chaplains/spiritual advisors. The response rate was 59%. Quantitative and qualitative analyses were carried out. Spiritual advisors describe their working patterns and understanding of their roles within the modern NHS, and their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…As a result, those citizens were able to find solace in the chaplains being present with them throughout their initial emotional hurt and pain. This, too, is consistent with research particularly surrounding chaplaincy care within hospitals, as a survey investigating the role and views of National Health Service spiritual advisors across the UK revealed that respondents highlighted the importance of presence and companionship and described these aspects of pastoral care as having “to do with unconditional acceptance of individuals, and with the dimension of ‘accompanying’ the patient in a supportive way instead of labelling and categorizing” (Lawrence et al., 2008: 282). It is clear that police chaplains can have a powerful presence in crisis situations when committed to serving as a ministry of presence that strategically leaves out communications surrounding religion.…”
Section: Resultssupporting
confidence: 69%
“…As a result, those citizens were able to find solace in the chaplains being present with them throughout their initial emotional hurt and pain. This, too, is consistent with research particularly surrounding chaplaincy care within hospitals, as a survey investigating the role and views of National Health Service spiritual advisors across the UK revealed that respondents highlighted the importance of presence and companionship and described these aspects of pastoral care as having “to do with unconditional acceptance of individuals, and with the dimension of ‘accompanying’ the patient in a supportive way instead of labelling and categorizing” (Lawrence et al., 2008: 282). It is clear that police chaplains can have a powerful presence in crisis situations when committed to serving as a ministry of presence that strategically leaves out communications surrounding religion.…”
Section: Resultssupporting
confidence: 69%